EVALUATION OF EDUCATION AND TRAINING PROGRAM FOR CIVIL SERVANTS: A NEW APPROACH TO IMPROVING EMPLOYEE PRODUCTIVITY - Deden Komar Priatna (Universitas Padjadjaran, 2020)
The purpose of this study was to determine the magnitude of the influence of the implementation of existing education and training programs on the work productivity of civil servants. Based on the results of data processing, it is known that the elements of implementing education and training programs that must be considered and improved are as follows: Training Materials, Non-Formal Education, Training Schedule, Instructor Hospitality, Training Variations, Training Methods, and Training Manuals. While the elements of the education and training program organizers that must be maintained are as follows: Formal Education, Instructor Skills, Instructor Capabilities, Training Facilities, Training Curriculum, Training Evaluation. The implementation of the education and training program has an effect on the work productivity of civil servants and the effect of the implementation of the education and training program is more dominant, this is because the implementation of the education and training program is more frequent and more applicable even though it still seems theoretical in the work of civil servants. Therefore, the right education and training program will have an impact on increasing the productivity of its employees.